2021
DOI: 10.1158/0008-5472.can-21-0736
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Chemically Modified, Synthetic, Triplex Peptide Nucleic Acid–Based Oncomir Inhibitors for Cancer Therapy

Abstract: miRNA-155 (miR-155) is overexpressed in various types of lymphomas and leukemias, suggesting that targeting miR-155 could be a potential platform for the development of precision medicine. Here, we tested the anticancer activity of novel, chemically modified, triplex peptide nucleic acid (PNA)–based antimiRs compared with the current state-of-the-art conventional full-length antimiRs. Next-generation modified PNAs that bound miR-155 by Watson–Crick and Hoogsteen domains possessed superior therapeutic efficacy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Chemically modified oligonucleotide small interfering RNAs and anti-miRs have been used to block the actions of specific endogenous genes and miRNA (25). More recently, LNA-anti-miR-132 has reduced liver fibrosis in a mouse model (26) LNA-anti-miR-150 reduced the renal infiltration of macrophages and polarization of M1/M2 macrophages in renal interstitial fibrosis mice.…”
Section: Discussionmentioning
confidence: 99%
“…Chemically modified oligonucleotide small interfering RNAs and anti-miRs have been used to block the actions of specific endogenous genes and miRNA (25). More recently, LNA-anti-miR-132 has reduced liver fibrosis in a mouse model (26) LNA-anti-miR-150 reduced the renal infiltration of macrophages and polarization of M1/M2 macrophages in renal interstitial fibrosis mice.…”
Section: Discussionmentioning
confidence: 99%
“…Gupta et al showed that γPNA delivered via polymeric nanoparticles antagonized the expression of miR-210 in a HeLa cancer model, resulting in an anticancer effect with no observed toxicities [154]. Our recent study has explored the potential of tail-clamp γPNA to improve the miR inhibition efficacy and decrease tumor progression in vivo [150].…”
Section: Gamma-modified Pna-based Mir Inhibitorsmentioning
confidence: 96%
“…γPNA is the only molecule known to invade duplex RNA/DNA composed of up to 100% CG content in a sequence-specific manner [53]. Another attractive γPNA design is tail-clamp modifications, which can be used to target miRNA-containing homopurine stretches [150].…”
Section: Gamma-modified Pna-based Mir Inhibitorsmentioning
confidence: 99%
“…A tetra-arginine-modified tail-clamp L Ser γPNA designed to target miRNA-155 was shown to exhibit superior anticancer activities in lymphoma cell lines and in mouse models over anti-miR-155 aegPNA and a control γPNA sequence. 313 Likewise, a 22nt miniPEG γPNA designed to target miRNA-210 can suppress tumor growth in mice much better than aegPNA with the same sequence and another miniPEG γPNA with a scrambled sequence when co-delivered with PLGA nanoparticles. 314 In a more elaborated control, an antisense miniPEG γPNA conjugated with pH-low insertion peptides (pHLIP) was shown to selectively target the DNA double-strand break repair factor KU80 in tumor cells thereby making them susceptible to irradiation.…”
Section: Introductionmentioning
confidence: 99%